Hedgehog signaling pathway regulates hexavalent chromium-induced liver fibrosis by activation of hepatic stellate cells. (1st March 2020) - Yan, Junyan; Huang, Huarong; Liu, Zuping; Shen, Jiayuan; Ni, Jian; Han, Jiwei; Wang, Renjun; Lin, Derong; Hu, Baowei; Jin, Lifang
Highlights: Chronic Cr(VI) treatment caused liver toxicity and fibrosis. Cr(VI) treatment activated hepatic stellate cells (HSCs). Cr(VI) treatment activated Hedgehog (Hh) signaling pathway-related molecules. In Shh +/− mice, HSC activation, Hh signaling and liver fibrosis were ameliorated. Abstract: With the spread of hexavalent chromium [Cr(VI)] contamination, risk of exposure in non-occupational populations is increasing. The liver is the main target organ for Cr(VI) accumulation; however, the effect of long-term Cr(VI) exposure on liver toxicity is largely unknown. In this study, we investigated the effect of chronic Cr(VI) exposure on liver fibrosis and its possible mechanism. Mice were injected with Cr(VI) for two months, and our results showed Cr(VI) treatment caused liver toxicity characterized by liver structure disorganization, liver dysfunction, and antioxidant enzyme system inhibition. The development of liver fibrosis was also found via the emergence of collagen fibril deposition, increased expression of extracellular matrix-related genes, activation of hepatic stellate cells (HSCs) and increase the expression levels of Hedgehog (Hh) signaling pathway-related molecules. To demonstrate the role of Hh signaling in the regulation of Cr(VI)-induced liver fibrosis, genetically modified mice with heterozygous deficiency of Shh ( Shh +/− ) were used. In the Shh +/− mice, Hh signaling, HSCs activation and liver fibrosis development were all ameliorated. In conclusion, we demonstrated that Cr(VI)-induced liver fibrosis development resulted from Hh pathway-mediated HSCs activation. Our findings strongly suggest that inhibition of Hh pathway may help in the development of new strategies for Cr(VI)-associated liver fibrosis.